THE EFFECT OF ISLAMIC WORK ETHICS ON EMPLOYEE LOYALTY OF YAYASAN NURUL HAYAT SURABAYA - Sheila Ayu Pramesti Permatasari; Ririn Tri Ratnasari (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of Islamic work ethics on employee loyalty at Nurul Hayat Foundation in Surabaya. This study uses a quantitative approach. Data collection techniques are by distributing questionnaires to employees of Nurul Hayat Surabaya. The analysis technique used is SEM PLS by conducting a non-probability sampling technique used in sampling in this study, namely the purposive sampling technique. The results of this study indicate that Islamic work ethics has a significant influence on employee loyalty.Keywords: Ethics,  Employee Loyalty, Nurul HayatREFFERENCE Ahmad, Shukri dan Yusuf Owoyemi, Musa. (2012). The concept of Islamic work ethic: An analysis of some salient points in the prophetic tradition. International Journal of Business and Social Science, 3(20),116-123.Ali, A. (2001). Scaling an Islamic work ethics. The Journal of Social Psychology, 128(5), 575-83.Ali, A. J., & Al-Kazemi, A. A. (2007). Islamic work ethic in Kuwait. Cross Cultural Management: An International Journal, 14(2), 93–104.Ali, A.J., dan Owaihan, A.A. (2008). Islamic work ethic: A critical review. Cross Cultural Management: An International Journal, 15(1), 5-19.Anwar Prabu Mangkunegara. (2004). Manajemen sumber daya manusia perusahaan. Bandung: PT Remaja Rosdakarya.Chang, C. C., C. M. Chiu, et al. (2010). The effect of TQM practices on employee satisfaction and loyalty in government. Total Quality Management, 21(12), 1299-1314.Faqih, Ainur Rahim. (2011). Bimbingan dan Konseling dalam Islam. Jakarta: UII press.Hart, D. W. and J. A. Thompson. (2007). Untangling employee loyalty: A psychological contract perspective. Business Ethic Quarterly, 17(2), 297-323.Hasibuan, Malayu S.P. (2010). Manajemen sumber daya manusia. Jakarta: PT Bumi Aksara.Kirana, K.C., Ratnasari, R.T. (2017). Evaluasi kinerja sumber daya manusia (SDM). Yogyakarta: Gosyen Publishing.Marri, M.Y.K. (2012). The Impact of Islamic work ethics on job satisfaction and organizational commitment: A study of agriculture sector of Pakistan. IJJBBS, 2(12), 37-49.Sugiyono. (2012). Metode penelitian kuantitatif kualitatif dan R&D. Bandung: Alfabeta.